2022
DOI: 10.1002/htj.22737
|View full text |Cite
|
Sign up to set email alerts
|

Dual solution of heat transfer in hydromagnetic micropolar fluid flow over a stretching sheet in a porous media: A numerical approach

Abstract: In this study, the researcher looks at the heat transmission of an incompressible magnetohydrodynamics micropolar fluid across a moving stretched surface in a Darcian permeable medium. The proper boundary conditions are used to facilitate the numerical solution (bvp4c) of the transformed governing equations. Graphical discussions have been made of the influence of the physical parameters on the velocity, angular velocity (microrotation), and temperature, and the distributions are accentuated on the plots via M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The important role played by thermal radiation in their research contributes to a better understanding of fluid behavior. Last but not least, Hussain and Ahmed 25 added to the conversation by exploring how a magnetic field controls the motion along a stretched surface implanted in a material of pores in a fluid type of micropolar, furthering our understanding of this complex field of study. The unsteady MHD flow of Casson fluid through a porous channel has been investigated by Gangadhar et al 26 The influence of bioconvection on the flow behavior of Williamson nanofluid over a stretching cylinder was numerically investigated by Gangadhar et al 27 The time dependent flow of Powell Eyring nanofluid over a vertical stretching sheet with entropy minimization was analyzed by Gangadhar et al, 28 they reported that the rise in the Brinkman number and Reynolds number enhances the entropy of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The important role played by thermal radiation in their research contributes to a better understanding of fluid behavior. Last but not least, Hussain and Ahmed 25 added to the conversation by exploring how a magnetic field controls the motion along a stretched surface implanted in a material of pores in a fluid type of micropolar, furthering our understanding of this complex field of study. The unsteady MHD flow of Casson fluid through a porous channel has been investigated by Gangadhar et al 26 The influence of bioconvection on the flow behavior of Williamson nanofluid over a stretching cylinder was numerically investigated by Gangadhar et al 27 The time dependent flow of Powell Eyring nanofluid over a vertical stretching sheet with entropy minimization was analyzed by Gangadhar et al, 28 they reported that the rise in the Brinkman number and Reynolds number enhances the entropy of the system.…”
Section: Introductionmentioning
confidence: 99%